Implementation Of Contextual Teaching And Learning (CTL) In Learning English For Maritime At Barombong Maritime Polytechnic - Nasaruddin, Nurlely; Linarti, Avera (CV. Shofanah Media Berkah, 2025)
This study aimed to find out the implementation of Contextual Teaching and learning (CTL) in learning English for Maritime at Barombong Maritime Polytechnic. The author used descriptive research by applying a qualitative approach. The source of data was taken from observation, recording, and interview. The data was analyzed by using the interactive model of Miles, Huberman and Saldana, namely data collection, data condensation, data display, and drawing and verifying conclusions. The result of this study concluded that the lecturer applied the CTL approach through main steps, namely preparing the material, showing the topic of learning, explaining the topic, and asking some questions. The lecturer developed students’ mind through working, finding and constructing knowledge and skills; conducted inquiry activity for all topics; developed the questioning attitude of students; created learning community (learn in group); presented “model” as learning role; conducted reflection in the end of meeting; and conducted authentic assessment in different ways. The lecturer also encouraged and motivated students by giving good feedback to students and connecting the topic of learning to real life.